KARAKTERISTIK FISIK BUBUK KUNYIT (Curcuma domestica Val.) HASIL PENGERINGAN OVEN KONVEKSI - Dian Purbasari; Lisa Pujiana (JURNAL AGROTEKNOLOGI, 2022)
The water content in fresh turmeric is quite high so it is easily damaged. For this reason, this research is necessary as an effort to handle post-harvest which will increase the shelf life of turmeric. The purposes of this study were to determine the physical properties of turmeric and to determine the effect of differences in drying temperature and duration of flouring on the physical characteristics of turmeric powder. The procedure was started with cleaning and size reduction, drying at temperatures of 60, 70, and 80°C, flouring for 1, 3, and 5 minutes, sifting with no. mesh 60, and measurement of physical properties. Results showed that the lowest water content of turmeric flour dried on 80°C and the 1-minute flouring time was 8.11%. Based on the color analysis test, the drying temperature of 60°C and the time of flouring is 5 minutes with an L (lightness) value of 64.53, a value of 12.47, and b of 51.46. The highest bulk density value was 0,42 g/cm³, obtained from the treatment with a temperature of 60°C and a flouring duration of 3 minutes. The smallest angle of repose value was obtained from a drying temperature of 80°C with a flouring time of 1 minute, namely 42.96°. The highest oil absorption value was obtained from the 80°C temperature treatment and 1-minute flouring time, which was 1.74 mL/g. The most significant water absorption was obtained from the 80°C temperature treatment with 3 minutes of flouring, which was 4.82 mL/g. Based on the analysis of the ANOVA test in this study, the physical characteristics of turmeric powder that affected by drying temperature were only water content and in the correlation test it was found that the observed variables that correlated with temperature were moisture content, bulk density, angle of repose, oil absorption. Keywords: drying, physical characteristics, turmeric powder